To find the equation that describes the given sequence \(2, 8, 32, \ldots\), let's first analyze the pattern in the terms.
- The first term (for \(n = 1\)) is \(2\).
- The second term (for \(n = 2\)) is \(8\).
- The third term (for \(n = 3\)) is \(32\).
We notice that:
- \(2 = 2 \cdot 2^0\)
- \(8 = 2 \cdot 2^2\)
- \(32 = 2 \cdot 2^4\)
In each case, we can rewrite the terms as:
- \(a_1 = 2 \cdot 2^{(n-1) \cdot 2}\)
From this, we can determine the formula for the \(n\)th term as follows:
\[ a_n = 2 \cdot 2^{(n-1) \cdot 2} \]
This simplifies to:
\[ a_n = 2^{2n - 1} \]
Thus, we can write the equation for the \(n\)th term of the sequence as:
\[ a_n = 2^{2n - 1} \]
So, the final answer is:
\[ a_n = 2^{2n - 1} \]